2014
DOI: 10.1021/es5027689
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Environmental Impacts of Wastewater-Based Algal Biofuels

Abstract: Recent research has proposed integrating wastewater treatment with algae cultivation as a way of producing algal biofuels at a commercial scale more sustainably. This study evaluates the environmental performance of wastewater-based algal biofuels with a well-to-wheel life cycle assessment (LCA). Production pathways examined include different nutrient sources (municipal wastewater influent to the activated sludge process, centrate from the sludge drying process, swine manure, and freshwater with synthetic fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…As a downside, wastewater is prone to production of undesirable viruses and bacteria which can result in contamination and will increase cleaning and maintenance costs [65]. Considerable improvement in current production technologies are also required to make large-scale wastewater algal biofuel systems possible [66]. In addition, feasibility of the system with respect to available land area around wastewater treatment plants and infrastructure requirements, such as effluent storage and transportation, should be thoroughly examined [43].…”
Section: Water and Nutrientsmentioning
confidence: 99%
“…As a downside, wastewater is prone to production of undesirable viruses and bacteria which can result in contamination and will increase cleaning and maintenance costs [65]. Considerable improvement in current production technologies are also required to make large-scale wastewater algal biofuel systems possible [66]. In addition, feasibility of the system with respect to available land area around wastewater treatment plants and infrastructure requirements, such as effluent storage and transportation, should be thoroughly examined [43].…”
Section: Water and Nutrientsmentioning
confidence: 99%
“…Regardless of the strain used (salt or fresh water), a nonsaline water supply will be required to make up for evaporative loss in an open-pond cultivation system. Lastly, off-setting part or all of the nutrient supply required to grow microalgae with non-petroleum-derived fertilizer such as municipal wastewater can help improve the carbon budget of microalgal-based biofuel production systems (Chisti, 2007;Wang et al, 2010;Bhatt et al, 2014;Dong et al, 2014;Mu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the wastewater could be used in its raw state or with minimal treatment so as to reduce the costs of the wastewater treatment plant (WWTP) (Pittman et al, 2011;Bhatt et al, 2014;Mu et al, 2014). Centrate, the liquid fraction after anaerobic digestion, offers a feed stream high in nitrogen and phosphorous, which are two of the main nutrients required for microalgae and also two compounds that cause high removal costs for most municipal WWTPs (Wang et al, 2010;Li et al, 2011a;Bhatt et al, 2014;Dong et al, 2014;Mu et al, 2014). In addition to decreasing the nutrient load to the plant, diverting centrate to algae production also decreases the treatment volume, thereby decreasing treatment costs of other chemical constituents (Li et al, 2011a;Mu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al (2011) calculated that 90% of freshwater, 94% of nitrogen and 100% of potassium, magnesium and sulfur could be saved when producing microalgal biofuels using wastewater as growth medium, and Mu et al (2013) confirmed the higher sustainability performance of microalgae grown in wastewater than cultures grown in freshwater.…”
Section: Present and Future Trendsmentioning
confidence: 99%